Faktor Penyebab Tidak Terpenuhinya Rasa Keadilan Pada Putusan NOMOR:9/PID.PRA.PRADILAN/2018/PN.GTO Di Pengadilan Negeri Gorontalo Kelas IA - Sri Hardiyana Diu; Suwitno Yutye Imran; Avelia Rahmah Y. Mantali (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This research aims to identify and analyze the factors that cause the sense of justice not to be fulfilled in decision Number: 9/Pid.Pra.Pradilan/2018/Pn.Gto at the Class IA Gorontalo District Court. This research is classified as empirical research using descriptive analysis methods. Data was obtained through the study of court decision documents, analysis of legal literature, and interviews with legal experts and judicial practitioners. This research allows researchers to get a comprehensive picture of the issues faced in this case. The results of this research show that several important factors cause a sense of justice to be fulfilled in a judge's decision.